2012
DOI: 10.1093/treephys/tpr130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four phloem-specific promoters in vegetative tissues of transgenic citrus plants

Abstract: 'Mexican' lime (Citrus aurantifolia Swingle) was transformed with constructs that contained chimeric promoter-gus gene fusions of phloem-specific rolC promoter of Agrobacterium rhizogenes, Arabidopsis thaliana sucrose-H(+) symporter (AtSUC2) gene promoter of Arabidopsis thaliana, rice tungro bacilliform virus (RTBV) promoter and sucrose synthase l (RSs1) gene promoter of Oryza sativa (rice). Histochemical β-glucuronidase (GUS) analysis revealed vascular-specific expression of the GUS protein in citrus. The RTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 51 publications
1
31
0
13
Order By: Relevance
“…Miyata et al (2012) demonstrated specific GUS expression driven by the AtPP2 promoter in phloem tissue of transgenic sweet orange. However, uidA gene expression driven by this type of promoter, quantified by qPCR, is relatively lower when compared to genes driven by constitutive promoters (Dutt et al, 2012;Benyon et al, 2013).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Miyata et al (2012) demonstrated specific GUS expression driven by the AtPP2 promoter in phloem tissue of transgenic sweet orange. However, uidA gene expression driven by this type of promoter, quantified by qPCR, is relatively lower when compared to genes driven by constitutive promoters (Dutt et al, 2012;Benyon et al, 2013).…”
Section: Resultsmentioning
confidence: 91%
“…Noticeably, no event showed gene silencing according to the qPCR analysis results because all transformation events presented gene expression. Gene silencing is typically detected in plants with multiple copies integrated at one or several loci; however, gene silencing was not reported in citrus plants with up to four transgene copies (Dutt et al, 2012;Benyon et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations